Integrating Comic into Biology Education Handout: Enhancing Reproductive Health Learning at SMA 1 Cawang Baru - Destri Natalia Aruan; Fajar Adinugraha; Adisti Ratnapuri; Novi Setiati (Pro-Life, 2025)
Reproductive health education is often challenging and unengaging, particularly for adolescents undergoing puberty. The lack of interactive and entertaining teaching materials further hinders effective learning. This study aims to develop and evaluate a comic-integrated handout on reproductive health for students at SMA 1 Cawang Baru. In this study, the research and development (R&D) approach was employed following Sugiyono's development model. The comic-integrated handout combines material content, comic-based entertainment, educational video links, and online tests. Validation results indicated feasibility scores of 75% (linguist), 78.33% (material expert), and 86.61% (media expert). Students' comprehension in the high category increased from 5.13% to 69.23%, while the low category decreased from 84.61% to 12.82%. Test scores improved from 44.62 to 81.03, with an overall perception score of 84.55% categorized as "Strongly Positive". These findings indicate that the comic-integrated handout is a potential and promising educational tool that improves student engagement and understanding. Therefore, we suggest this approach could be applied in future studies that focus on refining contextual relevance and expanding the approach's implementation across various educational settings.